ADCC: An underappreciated correlate of cross-protection against influenza? - de Vries, Rory D.; Hoschler, Katja; Rimmelzwaan, Guus F. (Frontiers in Immunology, 2023)
In this short review, we summarized the results obtained with an assay to detect influenza virus-specific antibodies that mediate ADCC, which was developed and evaluated within the framework of the IMI-funded project “FLUCOP”. HA-specific ADCC mediating antibodies were detected in serum samples from children and adults pre- and post-vaccination with monovalent, trivalent, or quadrivalent seasonal influenza vaccines, or following infection with H1N1pdm09 virus. Additionally, using chimeric influenza HA proteins, the presence of HA-stalk-specific ADCC mediating antibodies after vaccination and natural infection with H1N1pdm09 virus was demonstrated. With serum samples obtained from children that experienced a primary infection with an influenza B virus, we showed that primary infection induces HA-specific ADCC-mediating antibodies that cross-reacted with HA from influenza B viruses from the heterologous lineage. These cross-reactive antibodies were found to be directed to the HA stalk region. Antibodies directed to the influenza B virus HA head mediated low levels of ADCC. Finally, vaccination with a recombinant modified vaccinia virus Ankara expressing the HA gene of a clade 1 A(H5N1) highly pathogenic avian influenza virus led to the induction of ADCC-mediating antibodies, which cross-reacted with H5 viruses of antigenically distinct clades. Taken together, it is clear that virus-specific antibodies induced by infection or vaccination have immunological functionalities in addition to neutralization. These functionalities could contribute to protective immunity. The functional profiling of vaccine-induced antibodies may provide further insight into the effector functions of virus-specific antibodies and their contribution to virus-specific immunity.